‘WE ALL ARE PERFECTLY IMPERFECT’: AN INTERPERSONAL METAFUNCTION OF MUNIBA MAZARI’S SPEECH IN A CASE ON SYSTEMIC FUNCTIONAL LINGUISTICS - Simanjuntak, Narambean; Simaremare, Rodia Mestina; Saputra, Nanda; Ngongo, Magdalena; Herman, Herman (English Review: Journal of English Education, 2022)
This study aims to find out the elements of the interpersonal function used in Muniba Mazari's speech and to find out the most dominant elements of interpersonal function. The source of data takes from a video of Muniba Mazari's speech that was examined by the researcher. The data of this research are clauses that have an element of interpersonal function spoken by Muniba Mazari’s speech. The instrument of data collection used is documentation in the form of video recording, and for technique of data collection is documentation method. To analyze the data involves four steps namely: data collection, data condensation, data display, and the last conclusion drawing. Based on the result findings of this research, the frequency of the subject 231 (25,41%), finite 173 (19,03%), while residue elements predicator 204 (22,44%), complement 189 (20,79%), circumtantial adjunct 40 (4,40%), conjunctive adjunct 32 (3,53%), comment adjunct 25 (2,75%), and the last mood adjunct 15 (1,65%). The result showed the most dominant element interpersonal function structure used in Muniba Mazari’s speech is subject with the total percentage is 25,41%. Based on the results it can be concluded that this research can be used as insight and useful as a model to discuss interpersonal functions in a speech. And the researcher hopes that readers can increase their knowledge when conducted analyzing interpersonal functions in a speech because it is very important to know the meaning of each clause conveyed.